Glibenclamide Increases Nitric Oxide Levels and Decreases Oxidative Stress in an In Vitro Model of Preeclampsia - Nunes, Priscila Rezeck [UNESP]; Bueno Pereira, Thaina Omia [UNESP]; Bertozzi Matheus, Mariana [UNESP]; Grandini, Nubia Alves [UNESP]; Siqueira, Juliana Silva [UNESP]; Corrêa, Camila Renata [UNESP]; Abbade, Joelcio Francisco [UNESP]; Sandrim, Valeria Cristina [UNESP] (MDPI, 2022)
(1) Background: The bioavailability of nitric oxide (NO) and oxidative stress are important events related to the pathophysiology of preeclampsia (PE). In this present study, we aimed to evaluate the antioxidant effect of glibenclamide (GB) on the NO synthesis, oxidative stress, and antioxidant capacity in endothelial cells incubated with plasma from preeclamptic (PE) and normotensive pregnant women (NT). (2) Methods: Human umbilical vein endothelial cells (HUVECs) were incubated with a plasma pool from 10 NT and 10 PE pregnant women; NO/NOx quantification and ROS levels were assessed by a fluorescence compound; lipid peroxidation was evaluated employing thiobarbituric acid (TBA); and total antioxidant capacity was measured by ferric reduction ability power (FRAP) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT). (3) Results: We found that endothelial cells incubated with plasma from PE showed lower NO and NOx levels compared with the NT group. However, GB treatment increased these levels, as well as the antioxidant capacity. Furthermore, a decrease was observed in ROS generation and lipid peroxidation (4) Conclusions: The GB treatment exerted a positive effect on the NO/NOx production by HUVEC incubated with plasma from NT and PE pregnant women, as well as in the reduction in oxidative stress and increase in the antioxidant capacity.
Keywords: antioxidant capacity; glibenclamide; HUVEC; nitric oxide; preeclampsia; reactive oxygen species